Compilation of mapping resources in turbot (Scophthalmus maximus): A new integrated consensus genetic map - Hermida, Miguel (2013)
The turbot (Scophthalmus maximus) is a species of great relevance to European aquaculture and hence might benefit from enhanced genomic resources. The aim of this study was to integrate all previous turbot mapping resources to obtain a dense consensus genetic map. A total of 514 single nucleotide polymorphisms (SNP) and microsatellite markers from reported turbot genetic maps, were used for map construction. Among these markers, 487 (LOD score > 3), including 39% expressed sequence tag (EST)-linked and 61% anonymous, were integrated in 24 linkage groups. The linkage map comprised a total length of 1414 cM (1274.4 cM framework) with 3.3 cM (3.6 cM framework) inter-marker distance, representing an estimated genomic coverage of ~ 90%. This map was used to refine quantitative trait loci (QTL) screening for sex, because of the relevance of this trait for the turbot industry, which confirmed not only the main sex-determining region at linkage group (LG) 5, but also the involvement of additional significant genetic factors at other linkage groups. Comparative mapping supported the macrosyntenic pattern previously observed when comparing turbot and model fish genomes and enabled identification of candidate genes related to sexual development and reproduction at LG5, such as DNAJC19 and Sox2. The available number of markers in the turbot map could be easily increased to 592 because of the established correspondence between linkage groups of the two main genetic maps, thus approaching 1 marker/Mb based on the turbot genome size. This map represents a useful tool for evolutionary studies and for supporting ongoing marker-assisted selection programs in this species.